The Story of Us (In Memoriam) - Vinson, Lauren (Cornfield Review, 2017)
A poem of young love. Too shy to divulge in high school, they kindled their feelings for one another, while attending college at The Ohio State University. Five months after being asked out, together they passed away in a tragic house fire; their souls together for eternity. 2-5-13